Widening Participation – The end of the Road the academic and social journey’s of six final year undergraduates in a prestigious university - Duggan, Aoife (2009)
recent years much work and research has been carried out on identifying and overcoming the barriers to Higher Education for those from under-represented backgrounds. However, little research exists on these students once they enter university, their journeys through Higher Education and their final trajectories.